Quality Of Dumpling Crackers Produced From Purple Sweet Potato Flour Substitution - Andini, Resti; Holinesti, Rahmi (Universitas Negeri Padang, 2022)
This study aims to analyze the effect of purple sweet potato flour substitution on the quality of dumpling crackers with the addition of purple sweet potato flour as much as 5%, 10%, and 15%. This research was conducted at the Catering Workshop in August 2021. This type of research is a pure experimental study with a completely randomized design (CRD) method consisting of 4 treatments and 3 rehash. The object of this research is dumpling crackers with the addition of 5%, 10%, and 15% purple sweet potato flour. The independent variable in this study was purple sweet potato flour. The dependent variable of this research is the quality of the dumpling crackers produced including the shape, color, aroma, texture, and taste. Analysis of the data obtained from the organoleptic test involving 5 expert panelists, namely the lecturer of Family Welfare Science, Padang State University. The data analysis technique used is Analysis of Variance (ANOVA) to analyze sensory test data. The data that has been obtained is then tabulated in tabular form and analyzed according to the test of each data. Then the data analysis is carried out, if the data obtained by Fcount is greater than Ftable, then it is continued with Duncan's test. The results showed that the substitution of purple sweet potato flour had an effect on color, and had no effect on shape, aroma, texture, and taste. Based on the results, the best research was found in the treatment (X3) 15% with the categories of neat shape, purple color, fragrant aroma, crunchy texture, and savory taste, therefore for further research, it is recommended to use purple sweet potato flour with 15% substitution which produces good quality.